Pengaruh Aktivitas Penggunaan Energi terhadap Emisi CO2 (Studi Kasus: Sembilan Negara dengan Kumulatif Emisi Terbesar) - Shereen, Shereen; Laulita, Nasar Buntu (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2023)
The decline of the living environment is caused by the increasing pollution and damage to the environment, especially CO2 emissions. Given this situation, developed countries in the world are worried about excessive carbon dioxide emissions, because CO2 emissions are directly related to economic growth and energy consumption. Three sectors that have the highest emissions are the electricity sector at 42%, the transportation sector at 23%, and the housing sector at 6%. The purpose of this study was to examine the effect of energy consumption, gross domestic product, international trade, foreign direct investment, and urbanization on CO2 emissions from 1990-2014. The examination focused on countries, like the United States, China, Russia, Brazil, Indonesia, Germany, India, England. and Japan. To achieve this aim, this research used a quantitative approach. The data were gathered from secondary data obtained through a literature study on World Bank data. It involved panel data totaling 225 observations. The data were analyzed using panel linear regression analysis with the Fixed Effect Model (FEM). The results showed that the variables, such as energy and urbanization, had a positive and significant effect on CO2 emissions. Meanwhile, gross domestic product, international trade, and foreign direct investment had a negative and significant effect on CO2 emissions. Simultaneously, the independent variables affected the dependent variable.